Seleksi Beberapa Hasil Persilangan Genotipe Jagung (Zea mays L) Tipe Daun Tegak - Magfira, M; Sulfiani, S; Syah, Uswah Trywulan; Nurcaya, N; Efendi, Roy (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
This study aims to determine several genotypes of upright leaf-type maize with high production, in addition to knowing the genotypic characters obtained from the selection of upright leaf-type corn with closer spacing. The study was arranged as an experiment using a randomized block design (RBD) with the treatment of types of corn resulting from crosses. There were 6 genotypes tested, namely SU1, SU2, SU3, SU4, SU5, SU6, and 2 control genotypes namely SU7 (variety RK75) and SU8 (variety RK457). Genotypes were tested based on agronomic characteristics and yield. The results showed that the production of the tested and the control genotypes were not significantly different. However, the highest average production was found in the comparison genotype, especially the RK457 variety, which was 7.49 t/ha. The results of the selection of agronomic characters stated that the genotypes tested and the control genotypes showed no significantly different results on the characters of plant height, cob height, leaf length, leaf width, and leaf angle but significantly different on the stem diameter character. Genotype SU5 had an average stem diameter of 20.75 mm, not significantly different from genotype SU6 (18.95mm), RK457 (19.24 mm), and RK75 (17.79 mm). However, it was significantly different from the genotypes SU1 (16.35 mm), SU2 (14.40 mm), SU3 (16.05 mm), and SU4 (16.93 mm). The selection results for yield characteristics stated that the tested and control genotypes did not have significantly different characters.